Using translation as a pedagogical tool in EFL classroom among the pre-service teachers : a case study - Al-Kindi, Alghaliya Sulaiman Abdullah (Kulliyyah of education, International Islamic Univesity Malaysia, 2021)
The use of translation in English as a Foreign Language (EFL) teaching and learning has always been a debatable issue and continues to be unresolved due to its controversial nature; positive vs negative impact. The English language pedagogy in Oman is no exception. It had gone through similar controversies between the communicative approaches of English language pedagogy and the actual translation classroom practices. Hence, the current study generally aimed to investigate the issue of using translation in the EFL pedagogy from the viewpoint of the EFL teacher education at Sultan Qaboos University (SQU). Specifically, it examined the role of the translation courses in managing the phenomenon of using translation in the English language classrooms in Oman. The researcher employed a qualitative research method to explore in-depth the viewpoints of the immediate authorities responsible for the English teacher education programme at SQU, English teacher supervision, and English language curriculum at the Ministry of Education (MoE). The perspectives of the SQU English student teachers and English teachers were also explored to gather a comprehensive and broader understanding of the phenomenon under investigation. To reach a saturation point, a purposeful sample of four instructors from SQU Education and Arts Colleges and eight English Curriculum Officers and Senior Supervisors from the MoE were interviewed in a face-to-face mode. Additionally, the researcher approached a puposive sample of 17 SQU English student teachers and 18 English teachers, both males and females, for their field practice perspectives. The descriptive analysis of the research findings stressed the debatable nature of the phenomenon of using translation in the foreign language pedagogical context in Oman. It also emphasized the role of the teacher education programme towards a better understanding of the role of the native language in learning a foreign language, on one hand, and how to manage the native language to the best of the foreign language teaching and learning, on the other hand. The future implications of this research study are hoped to positively influence the development of EFL teaching, learning and supervision in Oman, in practice as in theory; in light of the reported realization of translation, beyond any doubt, as a resourceful tool by all the leading authorities of English language at MoE and SQU.